Vitamin D Levels in Chronic Kidney Disease Stage 3, 4, and 5 - David Kristianus; Rudi Supriyadi; Siska Wiramihardja (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Hypovitaminosis D is highly prevalent in chronic kidney disease (CKD). This conditionmay increase CKD progression and cause various complications, since kidney has a pivotal role in metabolizing the vitamin D. The aim of this study was to find the difference in vitamin D levels among CKD stage 3 to 5.Methods: A cross-sectional study involving patients aged over 18 years with CKD stage 3 to 5 who visited Dr. Hasan Sadikin General Hospital, Dustira Hospital, and Kidney Special Hospital Ny. R.A. Habibie in 2017 was conducted. CKD stages were determined based on glomerular filtration rate (GFR). Kruskal-Wallis test was used to analyzethe difference in vitamin D levels among CKD stage 3 to 5.Results: One hundred subjects consisting of 57 men and 43 women met the study criteria. There were 97% of subjects experienced hypovitaminosis D, with 20% having vitamin D insufficiency and 77% having vitamin D deficiency. In subjects with vitamin D insufficiency, a decrease in the mean vitamin D levels was observed along with advancing stages of CKD (p=0.255). No vitamin D level difference was observed among CKD stage 3 to 5 [11.1 (3.8-27.7) ng/mL vs 14.45 (5.10-50.90) ng/mL vs 11.7 (4.2-38.0) ng/mL, p>0.05].Conclusions: There is no difference in vitamin D levels among CKD stage 3, 4 and 5.